Pengelolaan BUM Desa Dalam Meningkatkan Perekonomian Masyarakat Desa Perspektif Siyasah Dusturiyah Dan Maliyah (Studi di desa Kertomulyo-Kecamatan Trangkil Kabupaten Pati) - Siti Nur Khotimah (Al-Balad: Journal of Constitutional Law, 2019)
Artikel ini bertujuan untuk mengkaji pengelolaan BUM Desa Kertomulyo yaitu BUM Desa Mekar Mulya yang masuk dalam kategori BUMDes terbaik se-kabupaten pati dalam membantu meningkatkan perekonomian masyarakat desa kertomulyo berdasarkan pespektif siyasah dustiriyah dan Maliyah. Hasil pembahasan artikel ini menunjukkan bahwa: 1) BUMDes Mekar mulya membentuk beberapa unit usaha dan dalam perspektif siyasah dusturiyah pengelolaannya telah berjalan sesesuai dengan peraturan yang ditetapkan pemerintah, begitu juga dengan peraturan desa kertomulyo No.2 Tahun 2013. Selanjutnya perspektif Siyasah Maliyah dikategorikan dalam baitul mall. 2) Faktor penghambat pengelolaan terbagi menjadi 2 faktor: eksternal dan internal. 3) Upaya yang dilakukakan diantaranya pemenuhan sarana dan prasarana sebagai penunjang kinerja dan pemberian pemahaman/sosialisasi kepada masyarakat desa mengenai program dari BUMDes yang akan memberikan manfaat dan menunjang perekonomian masyarakat desa kertomulyo. This study aims to examine the management of BUM Kertomulyo Village i.e. BUMDes Mekar Mulya, which is nominated as the best BUMDes in Pati regency in helping to improve the economy of the Kertomulyo village community be based the perspective of siyasah dustiriyah and maliyah This study is an empirical juridical type with a sociological juridical approach. The main data is primary data, which was obtained from interviews with informants while secondary data was obtained from official documents, journals, books, theses, and legislation that supports research results. The results of the discussion showed that: 1) BUMDes Mekar mulya was formed several business units to help increase the economy of a village community, whereas in siyasah dusturiyah perspective the management has already run following the regulations set by the government, as well as the Kertomulyo village regulation No.2 of 2013 concerning Establishment of BUMDes. then, the according to Siyasah Maliyah's perspective, it is categorized of Baitul Mall . 2) Inhibiting factors in the management of BUMDes Mekar Mulya are divided into two factors: external and internal. 3) The efforts undertaken by the Village Government to improve the economy of the village community in the management of Bumdes included the fulfillment of facilities and infrastructure as a support for performance and the provision of understanding/socialization to the village community regarding programs from BUMDes that will provide benefits and support the economy of the Kertomulyo village community.